2003
DOI: 10.1007/s10158-003-0027-z
|View full text |Cite
|
Sign up to set email alerts
|

Mode of action of atracotoxin at central and peripheral synapses of insects

Abstract: These studies characterized the paralytic and neurophysiological effects of an atracotoxin (ACTX), from the Australian funnel web spider, Hadronyche versuta, and compared it to the established P/Q-type calcium channel blocker, omega-agatoxin-IVA (omega-Aga-IVA). ACTX-induced paralysis was of a spastic form in housefly ( Musca domestica) larvae, but it was inactive on neuromuscular junction of housefly and tobacco budworm ( Heliothis virescens). On cockroach ( Periplaneta americana) cercal nerve-giant fiber syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 13 publications
2
39
0
Order By: Relevance
“…That is, in the LD 50 assays, the activity of a toxin depends not only on its intrinsic affinity for the target channel but also on its in vivo stability and its ability to penetrate anatomical barriers. The latter point is crucial in that -ACTXHv1a targets the central nervous system of insects (4,5), whereas most other spider toxins act presynaptically at insect neuromuscular junctions. Thus, a mutant toxin might have reduced activity not because of a reduced affinity for the target channel, but rather because of increased susceptibility to proteolysis or more limited access to the central nervous system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…That is, in the LD 50 assays, the activity of a toxin depends not only on its intrinsic affinity for the target channel but also on its in vivo stability and its ability to penetrate anatomical barriers. The latter point is crucial in that -ACTXHv1a targets the central nervous system of insects (4,5), whereas most other spider toxins act presynaptically at insect neuromuscular junctions. Thus, a mutant toxin might have reduced activity not because of a reduced affinity for the target channel, but rather because of increased susceptibility to proteolysis or more limited access to the central nervous system.…”
Section: Resultsmentioning
confidence: 99%
“…The phyletic specificity of these toxins appears to reside in their ability to block insect, but not vertebrate, voltage-gated calcium channels (2). Although nanomolar concentrations of -ACTX-Hv1a are sufficient to block high voltage-activated (HVA) calcium currents in the central nervous system of the fruit fly Drosophila melanogaster and the American cockroach Periplaneta americana (2,5), 1 M toxin does not block HVA calcium currents in vertebrate neurons (2) and the toxin is harmless when injected subcutaneously into newborn mice (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, this analysis indicates that 1T0Z (from the Asian scorpion Buthus martensi Karsch) and 1I25 (from the Chinese bird spider O. huwena) may have anti-coleopteran properties due to the fact that they are in the same branch as 1WWN and 1TI5, respectively ( Figure 1). Studies have shown that insecticidal toxins purified from arthropod venoms exert their effects via specific interactions with ion channels and receptors in the central or peripheral nervous system (De Lima et al, 2007;Bloomquist, 2003;Johnson et al, 1998;Fletcher et al, 1997). B. martensi Karsch venom has four peptides related to the excitatory insect toxin family and 10 related to the depressant insect toxin (Goudet et al, 2002).…”
Section: The Phylogenetic Relationship Of Insecticidal Toxins and Thementioning
confidence: 99%
“…124,126 In affected insects, ω-ACTX-Hv1a induces a slow-onset, irreversible spastic paralysis that precedes flaccid paralysis and death. 124,130 D. melanogaster that were engineered to express an inducible ω-ACTX-Hv1a transgene often developed a phenotype reminiscent of a hypomorphic allele of the dmca1D gene which encodes the Drosophila Ca V 1 channel. 131 This led to the suggestion that insect Ca V 1 channels are the primary target of ω-ACTX-Hv1a 131 , since similar phenotypes have not been reported for hypomorphic alleles of dmca1A.…”
Section: Peptide Toxins That Block Insect Ca V 1 Channelsmentioning
confidence: 99%